Role of KVKs in Strengthening Livelihood Security of Resource Poor Farm Families of Rural India - Nath, Sujit K; De, H K (Indian Journal of Extension Education, 2015)
KVKs are the ICAR sponsored district level organisations to test and popularise location specific frontier technologies  and thereby strengthening the rural agro-economic scenario of rural India. Till the end of 2014, ICAR has established a  network of 641 numbers of KVKs in the rural districts of India to cater the latest scientific needs of the farming community  which is in the way of erstwhile lab to land programme. An empirical comparison between various development  parameters, i.e. socio-economic, occupational, technological and environmental innovations by the resource poor farm  families of the adopted villages of KVK, Deogarh of Odisha state and its non-adopted villages in this study. It also  quantified the gap between adopted and non-adopted villages and observed significant gaps in some important indicators  i.e. cropping intensity (74.3%), crop diversification (48.7%), coordination among farmers (75.9%), avenues for agro employment facilities (69%), skill competency (68%) and reduction in migration (78%). In the components of  environment protection towards sustainable agriculture, the steps taken by the farmers were found to be inadequate. The  author apprehends that the impact of KVK in influencing the majority of farmers in the whole district in terms of adoption  of scientific farming practices may not be very effective.
Keywords: Environmental; impact of KVK; innovations; socio-economic; technological